The impact of fruits on the sensory acceptability of yogurt among Generation Z - Veljović Sonja; Vukolić Dragan; Gajić Tamara (Acta Agriculturae Serbica)
This study examines the influence of different types of fruits on the sensory acceptability of fruit yogurts among Generation Z. The research was conducted on a sample of 75 participants, employing sensory analysis to evaluate attributes such as taste, aroma, color, texture, and overall sensory acceptability. The results indicate that certain fruits have a statistically significant impact on sensory perception, with strawberries and raspberries receiving the highest scores, while peaches were rated the lowest, particularly in the color category. Aroma and color were identified as key predictors of overall sensory acceptability, demonstrating strong correlations. Differences among participants based on gender and place of residence underscore the importance of demographic characteristics in shaping preferences. These findings provide practical guidance for the food industry, highlighting the need for innovations in product aroma, color, and texture, as well as tailoring offerings to specific demographic groups. The study contributes to understanding the preferences of Generation Z and serves as a foundation for developing products aligned with their sensory and esthetic expectations.